Results of implementation of social rehabilitation technologies for people with lower extremity diseases/injuries - Usca, Svetlana; Lubkina, Velta; Kaupuzs, Aivars; Rizakova, Lorita (Social Welfare: Interdisciplinary Approach, 2013)
People with lower extremity diseases/injuries have limited mobility that affects their participation in socio-economic processes, including integration into the labour market. It is one of the risk groups that are exposed to the risk of social exclusion, and provision of the quality of their life requires the development of protection mechanisms. It is necessary to provide social rehabilitation and support services to facilitate their return to labour market and their involvement in all social activities alike other members of society. The article focuses on the provision of social rehabilitation services through innovative BIODEX SYSTEM 4, BIOSWAY and Vibro-massage facilities. The results of a linear research have been analysed and a description of case studies has been given.